Relative Resistance of Different Insecticides on Chilli Thrips, Scirtothrips dorsalis (Hood) in Andhra Pradesh - Vanisree, K.; Upendhar, S.; Rajasekhar, P.; Rao, G. Ramachandra (International Journal of Economic Plants, 2017)
The thrips population from Guntur district on chillies has developed high degree of resistance to various insecticides viz., monocrotophos, acephate, dimethoate, phosalone, carbaryl and triazophos followed by the population of Vizianagaram district with low levels of resistance implicating selection pressure and consequent resistance levels. The S. dorsalis population of Guntur district acquired resistance to the tune of 4.19 folds to monocrotophos, 5.62 folds to acephate, 5.59 folds to dimethoate, 6.80 folds to phosalone, 4.06 folds to carbaryl and 3.39 folds to triazophos at LC50 in comparison with the Vizianagaram district population.